2003
DOI: 10.1038/sj.bjc.6600669
|View full text |Cite
|
Sign up to set email alerts
|

Transformation induced by Ewing's sarcoma associated EWS/FLI-1 is suppressed by KRAB/FLI-1

Abstract: Ewing's sarcoma is a childhood bone tumour with poor prognosis, most commonly associated with a t(11;22)(q24;q12) reciprocal translocation that fuses the EWS and FLI-1 genes, resulting in the production of an aberrant chimeric transcription factor EWS/FLI-1. To elucidate the mechanisms by which EWS/FLI-1 mediates transformation in mouse models, we have generated a murine Ews/Fli-1 fusion protein. We demonstrate that this protein transforms fibroblast cells in vitro similar to human EWS/FLI-1 as demonstrated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…[65][66][67][68] In a previous CGH study, 38 8q was identified as a frequent site of amplification, above all in 'malignant' GISTs (until 57% of metastatic tumors). We have found amplification of CMYC only in three cases.…”
Section: Discussionmentioning
confidence: 99%
“…[65][66][67][68] In a previous CGH study, 38 8q was identified as a frequent site of amplification, above all in 'malignant' GISTs (until 57% of metastatic tumors). We have found amplification of CMYC only in three cases.…”
Section: Discussionmentioning
confidence: 99%
“…The use of techniques such as antisense oligonucleotides, dominant negative alleles, and transient siRNA transfections have been important preliminary approaches which have aided in this study. [30][31][32][33][34][35][36] However, the pitfalls inherent to these techniques have limited their usefulness. For example, antisense techniques can trigger a growth-inhibitory γ-interferon response due to the formation of double stranded RNA species (Ref.…”
Section: Retroviral Rnai To Study Ews/fli In Ewing's Sarcomamentioning
confidence: 99%
“…[25][26][27] Interestingly, this phenotype may be reversed by using a transcriptional repressor, which inhibits only the transcriptional activity of EWS/FLI-1, confirming that its oncogenic activity is related to the aberrant expression of specific EWS/FLI-1 target genes. 28 However, since its transforming activity is not only dependent upon the DNA-binding domain, it has been suggested that a protein-protein interaction may represent an additional FLI-1 oncogenetic mechanism. 29 Interestingly, up-regulation of c-myc is observed in the cell lines expressing EWS/FLI-1.…”
Section: Fli-1 Immunoreactivity In Round Cell and Vascular Tumors S Rmentioning
confidence: 99%